Shepard operator of least squares thin-plate spline type - CĂTINAȘ, Teodora; MALINA, Andra (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
We obtain some new Shepard type operators based on the classical, the modified Shepard methods and the least squares thin-plate spline function. Given some sets of points, we compute some representative subsets of knot points following an algorithm described by J. R. McMahon in 1986. Mathematics Subject Classification (2010): 41A05, 41A25, 41A80.